Mathematics and the Collision Regulations (Journal of navigation, 1962)
In the January number of the Journal (15, 104) Captain Wylie discussed the apparent conflict which existed between certain mariners and certain mathematicians about the efficacy of the Collision Regulations at sea. His contribution, which followed the publication in the October 1961 number (14, 379) of Mr. Calvert's ‘Comparison of Two Systems for Avoiding Collision’, was discussed in the same number by a selection of seamen and mathematicians. Followers of this controversy will be interested to read the remarks of Captain Weekes, printed on p. 271 on the subject of how imperfectly many ships' officers understand relative movement. Commander Clissold's suggestion, printed in the same discussion, that Calvert's and Hollingdale's rules should be tested on marine radar simulators is also to the point.